Digitalization of the insurance industry of Kazakhstan: problems, digital technologies, development paths - Sembekov, A.K. (BUKETOV BUSINESS REVIEW, 2020)
Object: The purpose of the study is to justify the objective need to transform the insurance industry of Kazakhstan using new technological digital solutions and to study the problems. According to the results of the study to consider reforming the insurance using digital technologies. Methods: During the study, the author used methods: observation, generalization, comparison, analysis, systematic approach, systematization of the materials, processing. Results: The article explores current trends in the insurance industry of Kazakhstan, using digital technologies. The concept of “digital insurance” is substantiated, the main factors of digitalization of the insurance industry are determined. Business processes of insurance activities of the company, which are subject to the use of digital technology, are specified. Digitalization implementation issues in the domestic insurance market are analyzed and priorities are identified. Conclusion: The author argues that the digital economy is a future economic model based on new productive forces. In this aspect, the issues of integrated digitalization of the financial (insurance) sector of the economy are relevant. The trends in the modern development of financial digitalization will radically change the regulatory functions of the state in the financial sector, the relationship between consumers of financial services and suppliers, creating new competitive opportunities.